Feed flavors in swine starter rations - Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nursing litters given a choice of flavored or unflavored diets responded by consuming more flavored diet. Pre-weaning feeding did alter the preference patterns of the post-weaned pigs. Pigs fed only basal ration as creep exhibited a varied preference pattern during the post-weaning preference trial. Pigs with access to flavored diet during the creep period exhibited a continued preference for the flavored diet during the post-weaning phase. Average daily feed intake, average daily gain, and the feed/gain ratios were similar for post-weaned pigs offered only flavored or control diet regardless of the pre-weaning treatment.
Swine Industry Day 1973 is known as Swine Day, 1973
Keywords: Swine; Feed flavors; Starter rations; pre-weaning treatment; Post-weaning treatment